Role of Epidural Electrode Stimulation in Three Patients with Incomplete AIS D Spinal Cord Injury - Yu-Chen Chen; Xiang-Ling Huang; Hung-Yu Cheng; Ciou-Chan Wu; Ming-Yung Wu; Lian-Cing Yan; Shin-Yuan Chen; Sheng-Tzung Tsai; Shinn-Zong Lin (Biomedicines)
Background/Objectives: To determine whether epidural electrical stimulation (EES) improves sensory recovery and walking function in patients with chronic spinal cord injury (SCI) with a grade on the American Spinal Cord Injury Association impairment scale (AIS) of C or D at the cervical level. Methods: Three individuals with cervical-level chronic AIS D SCI were enrolled in the study. The mean injury duration and age were 4.8 ± 4.5 (range: 1.5–10) and 56.7 ± 9 years, respectively. The participants received personalized electrical stimulation for 36 weeks and were evaluated for their SCI characteristics, the result of an AIS assessment according to the lower extremity sensorimotor scale, their muscle activity, and preoperative walking ability parameters, initially as well as at weeks 8 and 36 of the EES intervention. Results: Participants receiving EES significantly increased the muscle activity in most lower limb muscles. Regarding the AIS assessment of the lower extremities, one participant fully regained a light touch sensation, while two fully recovered their pinprick sensation (AIS sensory scores increased from 14 to 28). One participant achieved a full motor score, whereas the others’ scores increased by 19 and 7 points. Compared with preoperative gait parameters, two participants showed improvements in their walking speed and cadence. Walking symmetry, an important parameter for assessing walking function, improved by 68.7%, 88%, and 77% in the three participants, significantly improving the symmetry index (p = 0.003). Conclusions: Thus, EES may be an effective strategy for sensory impairment recovery, as well as muscular activity and strength improvement. These findings may facilitate stable walking in subjects with chronic incomplete SCI, but larger clinical trials are warranted. Clinical trial: NCT05433064.